Format Pengelolaan Dana Tabungan Haji Untuk Pembangunan Sektor Riil Melalui Skema Project Based Sukuk (PBS) Dalam Kajian Fikih - Huril ‘Aini (JES (Jurnal Ekonomi Syariah), 2020)
One form of sharia financial instrument that has been widely issued by both corporations and the state is sukuk, sharia bonds. Sukuk emphasizes investment income not on the interest rate, but on the level of income based on the level of profit sharing ratio the amount agreed upon by both parties (issuers and investors) at the time of the contract. The purpose of this research is to examine the implementation of the Project Based Sukuk (PBS) scheme of the hajj funding to fund the development of the real sector, especially infrastructure in Indonesia in the perspective of fiqh studies. In this study, the author conducts an analysis of the study of literature and scientific journals so as to produce a conclusion related to the application of PBS on hajj funding. This type of research is qualitative research. To obtain relevant data, data collection techniques such as rule review and literature study are used. The results show that the financing of infrastructure projects using PBS schemes sourced from hajj funds can be done with the following conditions: (1) sukuk issued in accordance with and fulfilling Islamic sharia rules and regulations (2) infrastructure benefits are primarily aimed at the welfare of prospective pilgrims and the general public (3) financing must be aimed at investment portfolios with low risk and provide guaranteed returns to maintain the security, usefulness and prudence of managing pilgrims funds (4) the majority of ulama agrees that the management of hajj savings funds may be invested in the project based sukuk. Keywords: project based sukuk, sharia bonds, hajj funding